Photocontrolled DNA minor groove interactions of imidazole/pyrrole polyamides - Müller, Sabrina; Paulus, Jannik; Mattay, Jochen; Ihmels, Heiko; Dodero, Veronica I.; Sewald, Norbert (Beilstein Journal of Organic Chemistry, 2020)
Azobenzenes are photoswitchable molecules capable of generating significant structural changes upon E-to-Z photoisomerization in peptides or small molecules, thereby controlling geometry and functionality. E-to-Z photoisomerization usually is achieved upon irradiation at 350 nm (π–π* transition), while the Z-to-E isomerization proceeds photochemically upon irradiation at >400 nm (n–π* transition) or thermally. Photoswitchable compounds have frequently been employed as modules, e.g., to control protein–DNA interactions. However, their use in conjunction with minor groove-binding imidazole/pyrrole (Im/Py) polyamides is yet unprecedented. Dervan-type Im/Py polyamides were equipped with an azobenzene unit, i.e., 3-(3-(aminomethyl)phenyl)azophenylacetic acid, as the linker between two Im/Py polyamide strands. Only the (Z)-azobenzene-containing polyamides bound to the minor groove of double-stranded DNA hairpins. Photoisomerization was exemplarily evaluated by 1H NMR experiments, while minor groove binding of the (Z)-azobenzene derivatives was proven by CD titration experiments. The resulting induced circular dichroism (ICD) bands of the bound ligands, together with the photometric determination of the dsDNA melting temperature, revealed a significant stabilization of the DNA upon association with the ligand. The (Z)-azobenzene acted as a building block inducing a reverse turn, which favored hydrogen bonds between the pyrrole/imidazole amide and the DNA bases. In contrast, the E-configured polyamides did not induce any ICD characteristic for minor groove binding. The incorporation of the photoswitchable azobenzene unit is a promising strategy to obtain photoswitchable Im/Py hairpin polyamides capable of interacting with the dsDNA minor groove only in the Z-configuration.
Keywords: azobenzene; DNA minor groove; N-methylimidazole; N-methylpyrrole; photoswitches; polyamide